Study of hardness properties of buttwelded joints using Shield Metal Arc Welding (SMAW) on mild steel plate / Nur Ain Syuhada Syafika Mohd Syukri - Mohd Syukri, Nur Ain Syuhada Syafika (2022)
This proposal focused on the SMAW (shield metal arc welding) butt welded joints' hardness properties on mild steel plate. SMAW is one of the most used welding techniques today, despite the fact that this particular form of SMAW welding is tough and challenging. This research article will continue the examination to establish whether this SMAW welding technique is suitable for welding mild steel. In this investigation, the mild steel plate will be welded using SMAW type welding and butt joint type. Using a Vickers hardness machine, the hardness value of the welded sample will be determined